The Oxford companion to wine (Oxford Univ. Press, 1994)
"Including contributions and advice from authorities around the world, Its 3,000 alphabetically arranged entries range from brief entries--What is a blanc de noirs? Where is Chateau Latour?--to fascinating longer essays on the intricacies of wine scoring, wine aging, and the nuances of judging a wine's color, aroma and flavor." -- from Publishers Description.